Comparative transcriptome analysis revealed omnivorous adaptation of the small intestine of Melinae - Lidong Wang (Nature Portfolio, 2021)
Abstract As the main digestive organ, the small intestine plays a vital role in the digestion of animals. At present, most of the research on animal feeding habits focuses on carnivores and herbivores. However, the mechanism of feeding and digestion in omnivores remains unclear. This study aims to reveal the molecular basis of the omnivorous adaptive evolution of Melinae by comparing the transcriptome of the small intestines of Asian Badgers (Meles leucurus) and Northern Hog Badgers (Arctonyx albogularis). We obtained high-quality small intestinal transcriptome data from these two species. Key genes and signalling pathways were analysed through Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and other databases. Research has mainly found that orthologous genes related to six enzymes have undergone adaptive evolution. In addition, the study also found three digestion-related pathways (cGMP-PKG, cAMP, and Hippo). They are related to the digestion and absorption of nutrients, the secretion of intestinal fluids, and the transport of food through the small intestine, which may help omnivorous animals adapt to an omnivorous diet. Our study provides insight into the adaptation of Melinae to omnivores and affords a valuable transcriptome resource for future research.